Commuting subsidies with two transport modes - Rainald Borck; Matthias Wrede (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study a simple model of commuting subsidies with two transport modes. City residents choose where to live and which mode to use. When all land is owned by city residents, one group gains from subsidies what the other loses. With absentee landownership, city residents as a group gain at the expense of landowners. Subsidies toward different modes have different effects, however, for instance, in one case, rich automobile drivers suffer from transit subsidies, while poor transit users may benefit from subsidies to automobiles.
Keywords: R14; R48; 330; Pendelverkehr; Verkehrssubvention; Verkehrsmittelwahl; Verteilungswirkung; Wohnstandort; Theorie